Analisis Hukum Tata Ruang di Indonesia: Tantangan dan Implementasi Dalam Pembangunan Berkelanjutan - Munthe, Benny Kenjiroh (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Spatial planning plays a crucial role in planning land use that is fair, efficient, and environmentally friendly. This research was conducted using a qualitative approach with descriptive analysis. Data was collected through observations, literature studies, and interviews with urban planners, communities, and local governments. Additionally, this study employs policy analysis to evaluate how effectively the implementation of the Regional Spatial Planning (RTRW) can be properly executed. The research findings show that, although spatial planning policies are regulated by law, non-compliance with RTRW, land-use conversion, and conflicts of interest between the government and the private sector are the major issues faced. Furthermore, a key barrier is the low level of public participation in land use monitoring. Therefore, to maintain the sustainability of land use, the government must be more proactive in oversight and increase public awareness. In conclusion, effective spatial planning implementation requires collaboration between the government, the private sector, and the community, as well as support from information technology such as Geographic Information Systems (GIS).